ANALYSIS OF DISTRIBUTION OF NO2 POLLUTANTS IN PT. X SANGGAU REGENCY, WEST KALIMANTAN - Istiqomah, Qolby; Irsan, Robby; Satria, Agum (Fakultas Teknik Universitas Tanjungpura, 2023)
Air pollution can come from natural activities and human activities. One type of pollutant that needs attention is air pollution caused by exhaust fumes from engine combustion and air pollution due to machines such as steam power plants. PT. X is a company engaged in the industrial sector that processes bauxite into alumina. PT. X is an example of an industry that uses coal and diesel-fired steam power plants for its factory operations. As a result of the fuel combustion process produces several exhaust gases, one of which is nitrogen dioxide, into the surrounding air. If the flue gas from the chimney exceeds the quality standard, it can pose a risk to workers and the surrounding community. Therefore, research was conducted on analyzing the distribution of NO2 pollutants from chimneys at PT. X. The data used are primary and secondary. The primary data is in the form of NO2 concentration in ambient air, while the secondary data is in wind direction and speed in one year. The known secondary data is then processed using the wrplot application so that the results are obtained in the form of the distribution of NO2 pollutants in the air. Based on the results of wind speed and direction data processing in Figure 1, it can be seen that the dominant wind direction blows from east to west with 699 occurrences, with wind speeds mostly occurring between 3.00